2019
DOI: 10.1259/bjr.20190283
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gold nanoparticle mediated radiation dose enhancement through synchronization of breast tumor cell population

Abstract: Objective: The incorporation of high atomic number materials such as gold nanoparticles (GNPs) into tumor cells is being tested to enhance the local radiotherapy (RT) dose. It is also known that the radiosensitivity of tumor cells depends on the phase of their cell cycle. Triple combination of GNPs, phase of tumor cell population, and RT for improved outcomes in cancer treatment. Methods: We used a double-thymidine block method for synchronization of the tumor cell population. GNPs of diameters 17 and 46 nm we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…The reduced accumulation of NPs in cells treated with 10 nM DTX, as compared to 0 nM DTX, could be due to the fragmented division seen in cells treated with 10 nM DTX ( Figure 2 f) [ 40 ]. The greater accumulation of NPs in cells treated with 50 nM DTX could be due to the cell cycle arrest in G2/M phase [ 20 , 40 , 41 ]. We also examined the NP accumulation when cells were treated with 1 nM DTX and observed an outcome much closer to the control and 10 nM conditions, as expected (see Supplementary Materials S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced accumulation of NPs in cells treated with 10 nM DTX, as compared to 0 nM DTX, could be due to the fragmented division seen in cells treated with 10 nM DTX ( Figure 2 f) [ 40 ]. The greater accumulation of NPs in cells treated with 50 nM DTX could be due to the cell cycle arrest in G2/M phase [ 20 , 40 , 41 ]. We also examined the NP accumulation when cells were treated with 1 nM DTX and observed an outcome much closer to the control and 10 nM conditions, as expected (see Supplementary Materials S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Manipulation of NPs' size and surface properties has been widely used to optimize the uptake of NPs in cancer cells in preclinical applications. Recent studies have exploited the cell cycle to further improve cellular NP uptake [20,21]. For example, arresting the cell cycle in the G2/M phase could result in a higher intracellular accumulation of NPs (see Figures S1-S3) [21].…”
Section: Introductionmentioning
confidence: 99%
“…peptide and PEG molecules were on the order of 2 kDa and smaller NPs were able to maximize the ligand-receptor interaction of RGD peptide using their higher surface curvature [76,85]. Various factors can affect the pharmacokinetics of the GNPs.…”
Section: Intracellular Fate Of Gold Nanoparticles Based On Their Physmentioning
confidence: 99%
“…Both in vitro and in vivo studies have demonstrated the synergistic effects of DTX when combined with radiotherapy [157,158]. Furthermore, it has been shown that the uptake of NPs, including GNPs, is increased when the cell population is synchronized in the G 2 /M phase [85,159]. This suggests the use of DTX concomitantly with other drugs or radiation, which was tested by Bannister et al as seen in Figure 8 [160].…”
Section: Rationale For Gold Nanoparticles In Chemoradiotherapymentioning
confidence: 99%
See 1 more Smart Citation